Rates of diagnostic genetic testing in a tertiary ocular genetics clinic. (3rd May 2020) - Lowery, R. Scott; Dehnel, John R.; Schaefer, G. Bradley; Uwaydat, Sami H.
ABSTRACT: Background: Clinical genetics has evolved significantly to become an efficient and effective means of diagnosing disease. Genetic treatments are now being developed which are showing promising results. However, ophthalmic patients are not utilizing genetic testing as part of their diagnostic workups. This paper explores the patient experience at the Ocular Genetics Clinic (OGC) at the University of Arkansas for Medical Sciences (UAMS) Jones Eye Institute and discusses reasons why patients continue to not pursue genetic testing. Materials and methods: We performed a retrospective chart review to understand the main reasons why patients were referred to the OGC between 2009 and 2018, with a detailed analysis of why patients did not pursue genetic testing. Results: Patients mainly did not undergo testing due to the cost of testing. However, patient availability, patient interest, and diagnostic workup also drove a significant amount of this lack of testing. Conclusions: Ocular genetic testing is becoming an increasingly beneficial tool for diagnosing ocular disease. However, to date, patients do not utilize this service fully. At the OGC, there are several main drivers for this lack of testing, namely finances, interest/availability, and diagnostic workup. As more ocular genetics clinics are established, it will be imperative to address reasons for forgoing genetic testing and to develop strategies to encourage patients to pursue this testing.